Psychological assessments, allostatic load and gene expression analyses in a randomized controlled trial comparing meditation, yoga, and stress education - Denninger, John W.; Joss, Diane; Romero, Perla M.; Khalsa, Sat Bir Singh; Hoge, Elizabeth A.; Bhasin, Manoj; Lazar, Sara W.; Dusek, Jeffery A.; Macklin, Eric; Libermann, Towia; Fricchione, Gregory L.; Benson, Herbert (Frontiers in Psychology, 2025)
ObjectivesThe mind–body research field has explored a broad range of outcome measures, however, there has not been systematic investigation on these outcome measures and there is little knowledge on what outcome measures can capture the differences between different mind–body practices. Therefore, this three-arm randomized controlled trial examined the effects of meditation vs. yoga vs. an active control condition of stress education, with a large battery of outcome measures including psychosocial self-report variables, allostatic load biomarkers, and gene expression measures.MethodsA total of 211 chronically stressed but otherwise healthy adults were randomized to 8-week one-on-one in-person interventions of meditation (N = 73), yoga (N = 68) or stress education (N = 70) interventions. Between-group differences in psychological outcome measurements, allostatic load biomarkers and genomic measures were compared at baseline (week 0), post-intervention (week 9), and at 26-week follow-up. Data were analyzed using a shared-baseline, two-way, repeated-measures ANOVA with unstructured within-person covariance over measurement timepoints. Treatment and time-specific effects were estimated using linear contrasts of adjusted means. False discovery rate correction was applied for multiple comparisons.ResultsNone of the outcome measures had significant differences among the three treatment arms. Within each treatment arm, most psychological questionnaire measures showed significant improvements (corrected p < 0.05). IL-6 showed slight elevation (but still within normal range for healthy adults) at the post-intervention timepoint within the stress education arm (corrected p < 0.05) and at the follow-up timepoint within the meditation arm (corrected p < 0.05). High density lipoprotein (HDL) levels were increased within the yoga arm at the follow-up timepoint (corrected p < 0.05). Post-intervention score changes of the Perceived Stress Scale (PSS) correlated with blood pressure changes in the meditation arm, insulin level changes in the yoga arm, and changes of allostatic load index in the control arm, none of which survived correction for multiple comparisons.ConclusionThis study did not find any significant between-group effects with any outcome measures. The null findings in this study might have been due to floor effects from the study sample of healthy adults.Clinical trial registrationhttps://clinicalTrials.gov, identifier: NCT01308970.